Fully automated satellite tracking system for directional antenna - Alam, Md. Mahbubul; Islam, Md. Monjurul; Mansoor, Ahmad Tamim (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.